Towards a university branding: the effect of self-efficacy on student development in a major higher institutions - Abdullah, Zulhamri; Ramlan, Mohd Fauzi; Sabran, Mohammad Shatar; Al-Sagoff, Syed Agil (Universiti Kebangsaan Malaysia, 2015)
The purpose of this study is to examine the effect of self-efficacy on student development in a higher learning institution, Universiti Putra Malaysia. There is an increase in figures in the unemployment rate of graduates was mainly due to the fact that most of the graduates were released to the labor market well trained in their areas of specialization but without being fully equipped with skills that are required in the highly competitive business environment. We used a Bandura's concept of self-efficacy as a measured framework of this study. A quantitative survey approach was employed in this study in Malaysia. The sampling frame was from a university's database provided by the Academic Department 2013. The findings showed that self-efficacy beliefs influence the goals which people set for themselves. Student-centered learning approaches employed activities to assist students to construct their own understandings and develop skills relevant to problem solving. These approaches were intended to promote development of learning skills, knowledge, attitudes and competencies for lifelong learning.